Differences in Men’s Body Dissatisfaction Based on the Type of Exercise Motivation - Maria Helena Suprapto; Mega Purnama Sari; Firmanto Adi Nurcahyo (ANIMA Indonesian Psychological Journal, 2015)
Exercising at a fitness center is one of the methods to obtain an ideal body shape.The purpose of this study was to determine whether there were differences in body dissatisfactions based on the type of exercise motivation. Participants were 100 male members of a fitness center who exercise at least twice a week for at least one hour per session. Measures used were body dissatisfaction questionnaire (Tylka, Bergeron, & Schwartz, 2005) and exercise motivation questionnaire by Markland and Tobin (cited in Vlachopoulos, 2012). Results showed a difference in body dissatisfaction between men with internal exercise motivation and those with external exercise motivation (Z = - 3.142, p < .05). Men who engaged exercises as driven by external exercise motivation had higher body dissatisfaction than those with internal motivation. This indicates that men with external exercise motivation were more dissatisfied with their body image, who were more likely to quit exercising if they did not obtain the expected result, or else they became obsessive with exercises because they was dissatisfied with their figures.